PERBANDINGAN EFISIENSI BANK PERKREDITAN RAKYAT DAN BANK UMUM DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS - Suliyanto Suliyanto; Dian Purnomo Jati (University of Merdeka Malang, 2014)
The purposes of this study were to measure and to compare levels of efficiency between commercial banks andrural banks. The data used in this study were taken from the banks financial statements published by theCentral Bank of Indonesia during 2009-2011. The sampling technique used was purposive sampling byanalyzing selected 10 commercial banks and 10 rural banks. The method used in this study was Data EnvelopmentAnalysis (DEA) and independent sample t test. Input variables used were deposit, personal expenses andassets, while output variables used were financing and income. The results showed that both commercial banksand rural banks were not efficient. The results of independent sample t-test showed that there was no significantdifference between levels efficiency of commercial banks and rural banks.